2021
DOI: 10.1111/jocn.15832
|View full text |Cite
|
Sign up to set email alerts
|

Models of support to family members during the trajectory of cancer: A scoping review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…The results also showed that some parents, after feeling emotionally, physically and nancially drained, wanted somebody to listen to their worries, fears and needs. This is in agreement with other qualitative research that reported reliance on friends, family and society for emotional support during home care of children with cancer (22)(23)(24).…”
Section: Cope Strategies Of Parents Whose Children Are Diagnosed With...supporting
confidence: 92%
“…The results also showed that some parents, after feeling emotionally, physically and nancially drained, wanted somebody to listen to their worries, fears and needs. This is in agreement with other qualitative research that reported reliance on friends, family and society for emotional support during home care of children with cancer (22)(23)(24).…”
Section: Cope Strategies Of Parents Whose Children Are Diagnosed With...supporting
confidence: 92%
“…Prior studies observed an important role of patients' family members in treatment acceptance 33 . However, there is also research showing that the inner‐familiarly relationships are individual and complex, and they may be supportive as well as obstructive 34 . Patients with a higher tumor stage (≥II) and, therefore, a worse prognosis tended to have a higher acceptance rate at the time of the data collection than patients with stage I BC.…”
Section: Discussionmentioning
confidence: 96%
“…33 However, there is also research showing that the innerfamiliarly relationships are individual and complex, and they may be supportive as well as obstructive. 34 Patients with a higher tumor stage (≥II) and, therefore, a worse prognosis tended to have a higher acceptance rate at the time of the data collection than patients with stage I BC. This result is plausible, as the benefit of AET is significantly higher in patients with worse prognosis.…”
Section: Acceptance and Non-modifiable Factorsmentioning
confidence: 95%
“…Family caregivers encounter a conflict between being caring duties and their own needs [ 54 ] which may explain increased caregiver cardiovascular and psychological morbidity [ 55 ] as well as increased all-cause mortality [ 56 ]. Family-specific interventions include psychological support, psychoeducation interventions and caregiver support [ 57 ].…”
Section: Discussionmentioning
confidence: 99%